Randomised clinical trial: addition of alginate‐antacid (Gaviscon Double Action) to proton pump inhibitor therapy in patients with breakthrough symptoms. Issue 12 (2nd May 2017) - Coyle, C.; Crawford, G.; Wilkinson, J.; Thomas, S. J.; Bytzer, P.
Summary: Background: Symptomatic breakthrough in proton pump inhibitor (PPI)‐treated gastro‐oesophageal reflux disease (GERD) patients is a common problem with a range of underlying causes. The nonsystemic, raft‐forming action of alginates may help resolve symptoms. Aim: To assess alginate‐antacid (Gaviscon Double Action, RB, Slough, UK) as add‐on therapy to once‐daily PPI for suppression of breakthrough reflux symptoms. Methods: In two randomised, double‐blind studies (exploratory, n=52; confirmatory, n=262), patients taking standard‐dose PPI who had breakthrough symptoms, assessed by Heartburn Reflux Dyspepsia Questionnaire (HRDQ), were randomised to add‐on Gaviscon or placebo (20 mL after meals and bedtime). The exploratory study endpoint was change in HRDQ score during treatment vs run‐in. The confirmatory study endpoint was "response" defined as ≥3 days reduction in the number of "bad" days (HRDQ [heartburn/regurgitation] >0.70) during treatment vs run‐in. Results: In the exploratory study, significantly greater reductions in HRDQ scores (heartburn/regurgitation) were observed in the Gaviscon vs placebo (least squares mean difference [95% CI] −2.10 [−3.71 to −0.48]; P =.012). Post hoc "responder" analysis of the exploratory study also revealed significantly more Gaviscon patients (75%) achieved ≥3 days reduction in "bad" days vs placebo patients (36%), P =.005. In the confirmatory study, symptomatic improvement was observed with add‐on Gaviscon (51%) but there was no significant difference in response vs placebo (48%) (OR (95% CI) 1.15 (0.69‐1.91), P =.5939). Conclusions: Adding Gaviscon to PPI reduced breakthrough GERD symptoms but a nearly equal response was observed for placebo. Response to intervention may vary according to whether symptoms are functional in origin. Abstract : Linked Content This article is linked to Katz and Coyle and Bytzer papers. To view these articles visithttps://doi.org/10.1111/apt.14120 andhttps://doi.org/10.1111/apt.14151 .